Presisi sebagai Inovasi dan Strategi Membangun Citra Kepolisian Daerah Sumatera Utara - Mulia Riadi; Dewi Kurniawati (PERSPEKTIF, 2022)
Innovation is the key to success in an organization. Without innovation the organization will not develop, it is aimed at improving the performance of public services. But as a lot of negative news about the police circulated, a bad image of the National Police has been formed in the society. General Listyo Sigit Prabowo first explained the concept of Presisi when undergoing due diligence and appropriateness of the candidate for the Chief of Police in Commission III of the DPR RI on January 20, 2021. This study aims to describe the innovation of the Presisi as a communication strategy for developing the image of the North Sumatra Regional Police to the community. This research is Qualitative research with unstructured observation methods and online data search / Internet Searching. The author finds that the North Sumatra Regional Police has realized 16 (Sixteen) Priority Programs and 8 (Eight) Commitments of the Chief of Police, General Listyo Sigit Prabowo.